Effects of MKP Concentration and Apical Pruning on the Growth and Yield of Melon (Cucumis melo L.) var. Inthanon under NFT Hydroponics System - Yuki Erwanto Putri; Ramdan Hidayat; Nova Triani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Melon (Cucumis melo L.) is a horticultural crop with high economic value, but its production is still low due to suboptimal cultivation techniques, especially in terms of fertilization and pruning. This study aims to determine the effect of monopotassium phosphate (MKP) fertilizer concentration and shoot pruning on the growth and yield of Inthanon melon variety. The study was conducted in the greenhouse, using a factorial Completely Randomized Design (CRD) with two factors, namely: MKP fertilizer concentration (0, 5, 10, and 15 g/L) and shoot pruning (internodes 25, 28, and 30). The results showed that the combination of MKP 15 g/L and pruning at the 30ᵗʰ internode gave the best results in terms of fruit weight and fruit flesh thickness. MKP 15 g/L fertilizer had a very significant effect on the parameters of plant length, stem diameter and number of leaves. Pruning shoots at the 30ᵗʰ internode increased the efficiency of assimilate distribution to the fruit. The application of MKP at 15 g/L combined with pruning at the 30ᵗʰ internode increased fruit weight 22.12% and fruit diameter 11.38% compared to control.